The Association Between Inflammatory Bowel Disease (IBD) and Thyroid Disorders: Systematic Review - Alyami, Abdullah Saleh Mohammed; Al Murdhimah , Yasir Ali S; Al Abyah , Ahemd Hussain A; Al Baahharith, Mohammed Hadi S; Al Rashah, Ahmed Mohseen Y; Al Murthimah, Ali Mohammed A; Almutairi, Shatha Abdulrahman m; AlYami, Faisal Hunaysh Abdullah; Al Makrami, Mohammed Ibrahim A; Al-Obayiah, Bader Mohamed A; Al Mardef, Nemer Nasser H; Al Yassain, Abdulrahman Mohammed M (Saudi Medical Horizons Journal, 2025)
Inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), is associated with various extraintestinal manifestations, including thyroid disorders. The relationship between IBD and thyroid dysfunction—such as hypothyroidism, hyperthyroidism, and thyroid cancer—remains unclear, with conflicting evidence on prevalence, risk factors, and underlying mechanisms. This systematic review followed PRISMA guidelines, analyzing studies from PubMed, Web of Science, Scopus, and Embase. Eligible studies included observational and genetic investigations on IBD and thyroid disorders. Data extraction and quality assessment were performed using the Newcastle-Ottawa Scale (NOS) and Cochrane Risk of Bias tools. Thirteen studies were included, revealing significant associations between IBD and thyroid disorders. Increased thyroid cancer risk in UC (SIR=10.34) and CD (SIR=10.45) patients. Reduced hypothyroidism prevalence in UC (OR=0.33) in some cohorts. Shared genetic pathways (e.g., IP-10 cytokine mediation) between IBD and autoimmune thyroid disease. Geographic and demographic variations, with higher malignancy risks in Asian IBD populations. IBD is associated with an elevated risk of thyroid disorders, particularly thyroid cancer, though hypothyroidism risk may vary by IBD subtype and population. Immune-mediated mechanisms, including cytokine dysregulation, likely contribute to these associations. Clinicians should consider thyroid screening in high-risk IBD patients, especially those with long-standing disease or specific demographic risk factors. Further research is needed to clarify causal pathways and the impact of IBD treatments on thyroid function.